Here today, gone tomorrow: Short‐term retention of pesticide‐induced tolerance in amphibians. (14th August 2015) - Jones, Devin K.; Relyea, Rick A.
Abstract Pesticide use has led to the ubiquitous contamination of natural habitats, which has inadvertently increased pesticide tolerance in target and nontarget species. Historically, increased pesticide tolerance has been attributed to natural selection for tolerance among individuals of affected populations. Recent research, however, has discovered that pesticide tolerance can be increased through phenotypic plasticity. Although induced pesticide tolerance may benefit organisms experiencing contaminated systems, little is known about its occurrence in vertebrates, its retention through ontogeny, or potential life history tradeoffs. Using time‐to‐death assays at 2 distinct developmental windows, the authors discovered that gray treefrog (Hyla versicolor) tadpoles exposed to sublethal concentrations (0 mg a.i./L, 0.5 mg a.i./L, and 1.0 mg a.i./L) of the insecticide Sevin® (carbaryl) early in life increased their pesticide tolerance to a lethal carbaryl concentration 5 d after sublethal exposure. However, this increased tolerance was not retained later in ontogeny (23 d post‐sublethal exposure). Moreover, no indication was found of pesticide‐induced treefrogs experiencing life‐history tradeoffs in terms of survival to metamorphosis, mass, or snout–vent length. Gray treefrogs are only the second vertebrate species and the second amphibian family to exhibit pesticide‐induced tolerance after sublethal exposure. The authors' data suggest that the ability to induce increased pesticide tolerance may play a critical role in amphibian survival in contaminated ecosystems. However, future work is needed to test the occurrence of inducible pesticide tolerance among numerous amphibian populations worldwide. Environ Toxicol Chem 2015;34:2295–2301. © 2015 SETAC